Education governance and the role of the headteacher: The new policy problem in Scottish education. (January 2022) - Forde, Christine; Torrance, Deirdre; Mitchell, Alison; McMahon, Margery; Harvie, Julie
As part of the current Review of Education Governance in Scotland, the Headteachers' Charter is perceived as a central policy solution. The Charter changes the responsibilities of the headteacher by altering the relationship between headteacher and local authority, and thereby bringing about changes to the governance of education. If these changes are perceived as the solution, what is the perceived policy problem? This article examines policy documents to explore the policy problem using Bacchi's (2012a) 'what's the problem represented to be' (WPR) approach, which uses a framework of six questions to analyse policy texts. The article begins with a brief overview of the policy programme, the 'Empowerment Agenda'. The article discusses Bacchi's WPR analysis framework and then presents the findings, using this framework. The article ends with a discussion of the impact of the reform of educational governance including the Headteachers' Charter on the role of the headteacher.